Inequity in the use of long-lasting insecticidal nets before and after nationwide mass distribution campaign in 48 districts of Uganda: VERSE toolkit analysis - Jaffer Okiring; Paul Katamba; Carol Kamya; Faith Namugaya; Geoff Lavoy; Gatien de Broucker; Anthony Ssebagereka; Elizabeth Ekirapa Kiracho; Joshua Mak; Bryan N. Patenaude (BMC Public Health)
Abstract Background Long-lasting insecticidal nets (LLINs) form a physical and chemical barrier against mosquitoes and have been shown to reduce malaria burden and mortality. Many countries, Uganda inclusive have distributed LLINs free of charge, drastically increasing LLIN ownership. However, ownership does not directly translate in to LLIN use. Methods Data from serial cross-sectional surveys were obtained from LLIN Evaluation in Uganda Project (LLINEUP); a cluster-randomized trial conducted in eastern and western Uganda. We apply the Vaccine Economics Research for Sustainability and Equity (VERSE) Toolkit to analyze LLIN usage and equity among household members before and after a nationwide mass distribution campaign in 48 districts. Results Overall, the proportion of household members who slept under a bed net a night prior to survey reduced from 85.4% (6 months), to 78.8% (12 months), and to 73.0% (at 18 months) following LLIN mass distribution campaign). The Wagstaff concentration indices were 0.131 at baseline and ranged between 0.023 to 0.051 between 6 and 18 months following the national LLIN campaign. This indicates that LLIN use is more prevalent amongst the more privileged people. At baseline, the Absolute Equity Gap (AEG) of 0.260 implied that the 20% most disadvantaged households would need to increase LLIN use by 26.0 percentage points to have similar levels as the top 20% most privileged households. Overall, inequity decomposition showed that relationship to household head was the major contributor to whether a household member slept under LLIN the previous night for their age in most timepoint with the exception at baseline. Conclusions LLIN use level significantly increased following a nationwide distribution campaign. It appears that respondent’s relationship with the household head explains most of the variation in LLIN use, while the least wealthy households seem to be dropping off at a faster rate in the use of LLINs following a nationwide distribution campaign. Strategies targeting LLIN use among the most disadvantaged households following a mass distribution campaigns are recommended.